Using Audiovisual Media to Improve Student Writing Skills at SMP Negeri 4 Ambon - Ferdinandus, Marcy Saartje (Pattimura Excellence Journal of Language and Culture, 2021)
Writing includes the ability to express students' opinions or be taught clearly and effectively in written form. Using audiovisual media can improve students writing skills. The purpose of this study is to find out the process and results of improving writing skills by using audiovisual media. The method used Class Action Research (CAR) with a qualitative approach. In collecting the data using observation and documentation. To analyze the success rate or percentage of student success after the teaching and learning process each cycle is done by providing the same evaluation in the form of written test questions at the end of each cycle. After the data is collected, data analysis is calculated using simple statistics that are to assess formative tests and learning completion. The result of the reduction of the data is presented in the form of a data display and then last concluded. The research procedures are planning, implementation, observation, and reflection. The results have shown the average student learning outcome was 72.33% and the number of students who had completed there was 25 children was 83.33%, and the unfinished 5 children (16.67%). This research was said to be successful if the average test score of students writing above KKM scores, which is 70, and students who score above KKM is at least 80%. At the end of Cycle 2 obtained data: the average student learning outcome was 72.33% and the number of students who had completed there was 25 children was 83.33%, and the unfinished 5 children (16.67%). So, based on data on cycle 2 of Class Action Research is said to have been successful. The findings showed that using audiovisual media could better give a positive effect on the motivation and attention of less active students. The result of this study is that audiovisual media in the form of animated videos can improve students' writing skills in English. Learning by using audiovisual media in the form of animated videos will awaken the spirit of student learning amid the saturation of online learning.